A Co‐ and Ni‐Free P2/O3 Biphasic Lithium Stabilized Layered Oxide for Sodium‐Ion Batteries and its Cycling Behavior. (21st August 2020) - Yang, Liangtao; del Amo, Juan Miguel López; Shadike, Zulipiya; Bak, Seong‐Min; Bonilla, Francisco; Galceran, Montserrat; Nayak, Prasant Kumar; Buchheim, Johannes Rolf; Yang, Xiao‐Qing; Rojo, Teófilo; Adelhelm, Philipp
Abstract: Cobalt‐ and nickel‐free cathode materials are desirable for developing low‐cost sodium‐ion batteries (SIBs). Compared to the single P‐type and O‐type structures, biphasic P/O structures become a topic of interest thanks to improved performance. However, the added complexity complicates the understanding of the storage mechanism and the phase behavior is still unclear, especially over consecutive cycling. Here, the properties of biphasic P2(34%)/O3(60%) Na0.8 Li0.2 Fe0.2 Mn0.6 O2 and its behavior at different states of charge/discharge are reported on. The material is composed of single phase O3 and P2/O3 biphasic particles. Sodium occupies the alkali layers, whereas lithium predominantly (95%) is located in the transition metal layer. An initial reversible capacity of 174 mAh g ‐1 is delivered with a retention of 82% dominated by Fe 3+ /Fe 4+ along with contributions from oxygen and partial Mn 3+/4+ redox. Cycling leads to complex phase transitions and ion migration. The biphasic nature is nevertheless preserved, with lithium acting as the structure stabilizer. Abstract : A Co‐ and Ni‐free layered oxide with a P2/O3 biphasic structure is prepared by using a sol‐gel method and used as the cathode for sodium ion batteries. Its electrochemical and structural properties, ion storage mechanism, phase transition, and ion migration are investigated using a set of techniques involving XRD, ssNMR, XANES, EXAFS before and after cycling.